The Implementation of Conventional Retailer Membership Cards In The Perspective of Islamic Business Ethics - Arifin, Zainal (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: The purpose of this research is to review the implementation of membership cards in buying and selling transactions at a conventional retailer in Metro City, Lampung, and its use in terms of Islamic business ethics.Design/Method/Approach: This qualitative field study uses primary and secondary data sources. The study used interviews, observation, and documentation to collect the data. In total, there were six respondents participated in this study. The collected data is then analyzed using inductive reasoning as the data analysis technique.Findings: Based on the research results, it was found that the member card implementation is used for a discount program obtained from collecting points from each transaction which can later be redeemed for various compensations and prizes. Such a scheme appears as a strategy to captivate customer in the form of loyalty issue. This finding indicates an incompatibility with the principles of Islamic business ethics. The implications of this research show that using member cards as a transaction attraction widely applied to various contemporary retailers is not in line with the principles of the sharia economics laws.Organally/Value: The novelty value(s) of this study concern filling the gap of how the member card strategy is seen from Islamic business ethics. The findings are expected to help business practitioners, policymakers, and academics to understand the implementation of various modern business strategies that do not conflict with Islamic characteristics.